On-line microchip electrophoresis-mediated preconcentration of cationic compounds utilizing cationic polyacrylamide gels fabricated by in situ photopolymerization. Issue 18 (28th August 2018) - Yamamoto, Sachio; Okada, Fuka; Kinoshita, Mitsuhiro; Suzuki, Shigeo
Abstract : A simple and efficient method was developed for the fabrication of a cationic sample preconcentrator on a channel of a commercial poly(methyl methacrylate) (PMMA) microchip. Abstract : A simple and efficient method was developed for the fabrication of a cationic sample preconcentrator on a channel of a commercial poly(methyl methacrylate) (PMMA) microchip. This approach is based on a simple photochemical copolymerization for the fabrication of a permselective preconcentrator. The intersection of the PMMA microchip was filled with a gel solution comprising acrylamide, N, N -methylene-bis-acrylamide, (3-acrylamidopropyl) trimethylammonium, and riboflavin that functioned as a photocatalytic initiator. In situ polymerization near the cross of the sample outlet channel was performed by pinpoint irradiation with a 488 nm SHG laser beam, which is also used as the light source for fluorimetric detection. The electrokinetic property and electric repulsion between sample components and cationic groups on the polyacrylamide gel layer enables trapping and preconcentration of cations at the boundary of the anodic side of the gel layer. Reproducibility is about 20% RSD due to the variation of the position of the hand-made electrode in sample reservoir, but the preconcentration factors exceeded over 10 4 -fold. The utility of the cationic preconcentrator gel was demonstrated by analyzing rhodamine derivatives, oligosaccharides labeled with rhodamine 110 and cytochrome C labeled with fluorescein isothiocyanate.